2006
DOI: 10.1175/jcli3745.1
|View full text |Cite
|
Sign up to set email alerts
|

Monsoon Regimes in the CCSM3

Abstract: Simulations of regional monsoon regimes, including the Indian, Australian, West African, South American, and North American monsoons, are described for the T85 version of the Community Climate System Model version 3 (CCSM3) and compared to observations and Atmospheric Model Intercomparison Project (AMIP)-type SST-forced simulations with the Community Atmospheric Model version 3 (CAM3) at T42 and T85. There are notable improvements in the regional aspects of the precipitation simulations in going to the higher-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
47
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(52 citation statements)
references
References 51 publications
(48 reference statements)
5
47
0
Order By: Relevance
“…Instead, tropical precipitation maxima reside over the Guinea coast and over the Gulf of Guinea. It has been hypothesized that simulated warmerthan-observed SSTs in the Gulf of Guinea are responsible for excessive rainfall south of the Guinea coast (Meehl et al, 2006). The comparison between CCSM2/T31x3a and CCSM3/T31 corroborates this hypothesis, since the Gulf of Guinea warm bias is much more pronounced in CCSM3/T31 than in CCSM2/T31x3a (cf.…”
Section: Comparisons With Ccsm3/t31supporting
confidence: 52%
“…Instead, tropical precipitation maxima reside over the Guinea coast and over the Gulf of Guinea. It has been hypothesized that simulated warmerthan-observed SSTs in the Gulf of Guinea are responsible for excessive rainfall south of the Guinea coast (Meehl et al, 2006). The comparison between CCSM2/T31x3a and CCSM3/T31 corroborates this hypothesis, since the Gulf of Guinea warm bias is much more pronounced in CCSM3/T31 than in CCSM2/T31x3a (cf.…”
Section: Comparisons With Ccsm3/t31supporting
confidence: 52%
“…CAM3 is designed to produce simulations with reasonable accuracy for various dynamical cores and horizontal resolutions (Collins et al, 2006;Hurrel et al, 2006;Meehl et al, 2006;). For this study semi-Lagrangian dynamical (SLD) core was used at 128×64 horizontal resolution with 26 vertical levels.…”
Section: Description Of the Modelmentioning
confidence: 99%
“…In fact, only a few of the global producing centers for long-range forecasts use these models for operational seasonal forecasting. Since it has been suggested that model performance may be a function of spatial resolution (Meehl et al 2006;Hurrel et al 2009) and ensemble size (Brown and Murphy 1996), other reasons for using two-tiered instead of coupled systems for operational forecasting include that the former system allows for the operational production of higher-resolution seasonal forecasts as well as larger ensemble forecasts since they are computationally less expensive than the latter. Moreover, when skillful SST forecasts are used, two-tiered systems may perform at least equally well as the current coupled systems (Troccoli et al 2008).…”
Section: Introductionmentioning
confidence: 99%